The Human Sanctity to Overcome Euthanasia and Abortion in Humanizing Humans Human - Maria Yunita; Emi Masruroh; Arsyad Muhammad; Sudrajat (Social Science Studies, 2022)
sanctity or human nature is an aspect that is able to reflect an act of humanizing humans, which is able to provide better morality to society. Not embedded in the value of human sanctity makes humans perform actions such as euthanasia and abortion. This research is a qualitative research with descriptive analysis technique withlibrary researchwhere this research tries to describe the existing phenomena, which are happening now or in the past. Human holiness makes a person reflected in the act of humanizing humans into things that need to be integrated into all aspects, no less important in terms of understanding human sanctity or self-nature.